MINERAL CONTENTS OF VARIOUS FLOUR TYPES PRODUCED IN DIFFERENT REGION OF TÜRKİYE - Raci EKİNCİ; Sezgin ÜNAL (Pamukkale University Journal of Engineering Sciences, 2002)
In this study, calcium, potassium, magnesium, iron, zinc, copper and mangan values of 86 wheat flour samples (30 Type 1, 30 Type 2 and 26 Type 3) from 30 different factories in 19 different city of 7 different region of Türkiye were examined. Significant differences in average mineral (potassium, magnesium, iron, mangan) values were observed among 86 flour samples in terms of flour types. Statistically, differences (variations) in other properties were not found important. Variations amon flour samples from different factories in minerals (calcium, potassium, iron, zinc, copper, mangan) were found to be statistically important.